The empowered village community development model South Konawe Regency coastal region (study of the underdeveloped village of the coastal region of South Konawe Regency) - Arif, La Ode Kasno; Taufik, Yani; Abadi, Musram (Anjoro: International Journal of Agriculture and Business, 2020)
Communities who lack the power and ability to manage existing resources are very vulnerable to poverty and find it challenging to achieve a better quality of life. The purpose of this study was to formulate a model of community empowerment in underdeveloped villages in the coastal area of ​​South Konawe Regency. The empowerment model of rural communities in coastal regions is designed by strengthening through the institutional system that must be played by the economic institutions in the village. The town is empowered to have alternative expertise so that financial resources are not focused on just one activity. The important thing that needs to be done is that empowerment activities for disadvantaged rural communities in coastal areas require collective action based on participatory, self-supporting, partnership, and sustainability approaches. The following needs to be supported by policies on the construction of rural environmental facilities and infrastructure, provision and strengthening of social and economic institutions in the village, improvement of human resource competencies, namely technical and managerial skills.